Analysis of the Causes of Divorce Suits From A Gender Perspective in the Religious Court of Selong, East Lombok - Suaeb, Suaeb; Lalu Supriadi Bin Mujib; Khairul Hamim (al-Afkar, Journal For Islamic Studies, 2025)
The increase in divorce reflects changes in society, which no longer considers divorce to be taboo, but rather a common phenomenon. This study aims to identify the factors causing divorce in the Selong Religious Court from a gender perspective and to analyze divorce rulings in the Selong Religious Court from the perspective of mubadalah theory. This study is a field study using a case study and legal-empirical approach, with primary data collected from court decisions and interviews with judges, as well as secondary data from legal references. The results of the study reveal that the factors causing divorce at the Selong Religious Court are economic problems, domestic violence, alcohol or drug dependence, neglect of one party, and prolonged disputes. The rulings in these cases align with the theory of mubadalah, encompassing five mutually supportive pillars: establishing a strong agreement as a trust from God, upholding the principles of partnership and reciprocity, regularly consulting with one another, treating each other with kindness, and creating comfort in interacting with one another.